Pre-Eruptive Coronal Resorption and Congenitally Missing Teeth in a Patient with Amelogenesis Imperfecta: A Case Report - Miloglu, Ozkan; Karaalioglu, Osman Fatih; Caglayan, Fatma; Yesil, Zeynep Duymus (European Journal of Dentistry, 2009)
This clinical report describes a male with autosomal recessive generalized hypoplastic amelogenesis imperfecta. This case is unusual in coronal resorptions prior to tooth eruption. This finding has been reported in some cases of autosomal recessive, autosomal dominant and X linked amelogenesis imperfecta (AI). In reported cases, the defects were usually small and occurred in a maximum of 2 teeth per person. In our case, pre-eruptive coronal resorptions affected three second molar teeth from both jaws. On the other hand; congenitally missing teeth and malocclusion were present in this case. Recall evaluations at 3 month intervals occurred for a period of 2 years and then prosthodontic management began. (Eur J Dent 2009;3:140-144)
Keywords: Amelogenesis imperfecta; Congenital missing teeth; Pre-eruptive coronal resorption; Malocclusion; Prosthetic restoration